2017
DOI: 10.1016/j.celrep.2017.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alternative Splicing on the Human Proteome

Abstract: SummaryAlternative splicing is a critical determinant of genome complexity and, by implication, is assumed to engender proteomic diversity. This notion has not been experimentally tested in a targeted, quantitative manner. Here, we have developed an integrative approach to ask whether perturbations in mRNA splicing patterns alter the composition of the proteome. We integrate RNA sequencing (RNA-seq) (to comprehensively report intron retention, differential transcript usage, and gene expression) with a data-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(151 citation statements)
references
References 62 publications
8
137
0
Order By: Relevance
“…We have developed an approach differentiating the major and unique AS isoforms for each AS group. Based on the abundance of the major transcript AS isoform, we confirmed that protein abundance is generally correlated to transcript AS levels in a spliceosome‐disrupted system (Larochelle, ; Liu et al , 2017b).…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…We have developed an approach differentiating the major and unique AS isoforms for each AS group. Based on the abundance of the major transcript AS isoform, we confirmed that protein abundance is generally correlated to transcript AS levels in a spliceosome‐disrupted system (Larochelle, ; Liu et al , 2017b).…”
Section: Introductionsupporting
confidence: 68%
“…We then sought to identify AS switch events (i.e., the most abundant splicing isoform changed between conditions) for P7‐to‐P50 on the transcriptome level and to map these events to the protein level. Using a tool called SwitchSeq (preprint: Gonzàlez‐Porta & Brazma, ; Liu et al , 2017b), we identified 900 switch events between HeLa P7 and P50. As depicted in Fig C, transcripts that underwent switching from a RI in P7 to protein coding in P50 (i.e., RI to coding) showed a significant increase on protein level in P50 ( n = 77, Wilcoxon test, P = 0.0071; Figs C and EV5D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational and in-vitro studies have provided evidence that a change in relative isoform abundances can lead to the production of protein variants that impact the network of proteinprotein interactions in different contexts (Buljan et al 2012;Yang et al 2016;Climente-González et al 2017;Wojtowicz et al 2007). In contrast, quantitative proteomics of naturally occurring proteins has identified much fewer protein variants than those predicted with RNA sequencing (Ezkurdia et al 2015;Liu et al 2017). Using state-of-the-art proteomics, it was recently shown that splicing changes at RNA level lead to changes in the sequence and abundance of proteins produced, although this was detected only for a limited number of transcripts (Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the establishment of the first large-scale proteogenomic study of breast cancer, more integrating genomic and proteomic data will be integrated to achieve a better picture of cancer biology. For instance, Liu et al could capture an unbiased quantitative snapshot of the constitutive and alternative splicing events on proteome by integrating RNA sequencing with the sequential window acquisition of all theoretical spectra-MS. Finding the RNA splicing links isoform expression in human transcriptome with proteomic diversity may help to study the perturbations associated with human diseases [11].…”
mentioning
confidence: 99%